Pes Planus Level and Foot Pain Affect Selected Performance Parameters: A Study on Team Sport Athletes - Irma Febriyanti; Hari Setijono; Fransisca Januarumi Marhaendra; Heryanto Nur Muhammad; Fatkhur Rohman Kafrawi; Faridha Nurhayati; Afifan Yulfadinata; Fifukha Dwi Khory; Ahmet Kurtoğlu; Amayra Tannoubi; Karuppasamy Govindasamy; Edi Setiawan (Balneo and PRM Research Journal)
Aims to investigate the relationship between pes planus (PP) with foot pain (FP) and performance in team sport athletes. Correlational research was adopted to reveal the relationship between PP with FP and performance. There were 84 athletes were involved in this research. Measurement of PP with footprint test (FT), FP with knee pain intensity-visual analogue scale (KPI-VAS) and performance with items 30m sprint (30ms), modified agility t-test (MATT), counter movement jump (CMJ), standing stock balance test (SSBT). We observed that FT-PP variable has a moderate negative correlation with FP-KPI-VAS (p = 0.003), which shows that PP significantly causes foot pain. In CMJ (p = 0.035) and SSBT (p = 0.004) there is a moderate negative correlation, which shows that the PP level reduced the level of power and balance. Meanwhile, there is a moderate positive correlation with 30mS (p < .001), and MATT (p < .001), which shows that the level of PP will reduce the level of running speed and agility. At the same time, FP-KPI-VAS had a small negative correlation with 30mS (p = 0.017), MATT (p = 0.017) and CMJ (p = 0.048). Finally, FP-KPI-VAS was found to have a large positive correlation with SSBT (p < .001). Thus, we confirm that PP is significantly correlated with FP and performance related to 30ms, MATT, CMJ, SSBT in team sports athletes